Robotic Christmas Activities with Beebot: A STEM Application for Preschool Education - Samara, V.; Kotsis, K. T. (Journal of Science Education Research, 2025)
This study aimed to explore the application of STEM as a learning tool in preschool education, focusing on creating engaging and effective teaching experiences. The research was conducted in a kindergarten in Greece, involving 44 students from both morning and full-day sections. The study employed a didactic intervention themed around Christmas, utilizing Beebot, an educational robot, to facilitate six activities over one week. These activities were designed to maintain children's interest by embedding them in a topical and meaningful context, encouraging critical thinking and teamwork. The research method involved hands-on activities where children operated Beebot to complete missions, fostering their digital skills and collaborative abilities. The intervention aimed to introduce young learners to abstract concepts through concrete experiences, enhancing their understanding of magnetism, number sequences, and environmental awareness. The study also emphasized the importance of teamwork, as children worked in groups to achieve common goals, thereby improving their social skills and learning performance. In conclusion, the study demonstrated that integrating STEM activities in early childhood education is imperative for developing critical thinking and adaptability in young learners. Educational robotics, like Beebot, proved to be an effective tool in creating an engaging learning environment, paving the way for the development of future flexible and innovative citizens.